Risk of childhood otitis media with focus on potentially modifiable factors: A Danish follow-up cohort study. (March 2018) - Kørvel-Hanquist, Asbjørn; Koch, Anders; Lous, Jørgen; Olsen, Sjurdur Frodi; Homøe, Preben
Abstract: Introduction: Otitis media is the primary cause of antibiotic prescription in children. Two-thirds of all children experience at least one episode of otitis media before the age of 7 years. The aim of this study was to characterise the attributable effect of several modifiable risk exposures on the risk of >3 episodes of otitis media at age 18 months and 7 years within a large prospective national birth cohort. Methods: The study used the Danish National Birth Cohort comprising information about otitis media and risk exposures from more than 50, 000 mother-child pairs from the period 1996–2002. Logistic regression models were used to estimate odds ratios for the risk factors and to calculate the population attributable fraction. Results: Short time with breastfeeding, early introduction to daycare, cesarean section, and low compliance to the national vaccination program were all associated with an increased risk of >3 episodes of otitis media at 18 months of age and at 7 years of age. The fraction of children with otitis media attributed from breastfeeding lasting for less than 6 months was 10%. Introduction to daycare before the age of 12 months attributed with 20% of the cases of >3 episodes of otitis media. Conclusions: Short duration of breastfeeding, early introduction into daycare, cesarean section, and low compliance with the national vaccination program increased the risk of experiencing >3 episodes of otitis media at 18 months, and at 7 years of age. These are factors that all can be modulated.